pharmaceutical-sciences 2018
DOI: 10.4172/pharmaceutical-sciences.1000335
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiretroviral Activity of 6-Acetyl-coumarin Derivatives against HIV-1 Infection

Abstract: Srivastav, et al.: Synthesis and Antiretroviral Activity of 6-Acetyl-coumarin Derivatives A series of 6-acetyl-coumarin derivatives (2a-n) were synthesized and evaluated for antiretroviral activity in C8166 T-cell line infected with HxBru-Gluc strain of human immunodeficiency virus-1. Michael Addition followed by re-aromatization and subsequent acid-induced elimination of water leads to the formation of coumarin intermediate, which undergoes Claisen-Schmidt condensation with substituted bezaldehydes using sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Anti-viral action and mechanism of 6-acetyl-coumarin analogues have been studied on human C8166 cells. It has been found that electronegative substituent at the phenyl ring connected with coumarin central motif plays a very important role in the anti-HIV activity of coumarin [46]. Further, QSAR and Docking approaches indicated that Coumarin negatively regulates 3' processing and integrase enzyme of HIV.…”
Section: Anti-hivmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-viral action and mechanism of 6-acetyl-coumarin analogues have been studied on human C8166 cells. It has been found that electronegative substituent at the phenyl ring connected with coumarin central motif plays a very important role in the anti-HIV activity of coumarin [46]. Further, QSAR and Docking approaches indicated that Coumarin negatively regulates 3' processing and integrase enzyme of HIV.…”
Section: Anti-hivmentioning
confidence: 99%
“…Further, expression of the HIV-1 receptor (CD4) and co-receptors (CXCR4 and CCR5) was downregulated which may also contribute to blocking the HIV entry [53,55]. 4-phenylcoumarin derivatives called neoflavanoids were synthesized and their anti-HIV effects were assessed on MT-2 infected cells in vitro [46]. It suggested that the acyl group was essential for the inhibition of both the Tat and NF-kB pathway [56].…”
Section: Anti-hivmentioning
confidence: 99%
“…To determine these activities, an enormous number of synthesized coumarin derivatives are subjected to various assaying. They showed a remarkably wide spectrum of antimicrobial (Al-Haiza et al, 2003;Medimagh-Saidana et al, 2015;López-Rojas et al, 2018), antifungal (Guerra et al, 2015;Forezi et al, 2018), anti-HIV (Kirkiacharian et al, 2002;Su et al, 2006;Srivastav et al, 2018), anticoagulant (Manolov & Danchev, 1999), antitumor (Nofal et al, 2000;Fayed et al, 2019) and anti-inflammatory (Kontogiorgis & Hadjipavlou-Litina, 2005). Also, many coumarin derivatives are used as optical brightening agents and food supplements (Wang et al, 2013;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their broad ranges of biological activities, they have also enjoyed laboratory preparation both in micro-scale and large-scale media. Coumarin and its fused derivatives have been reported to possess diverse pharmacological activities such as antimicrobial (Widelski et al, 2018), anticancer (Bouhenna et al, 2018), anti-inflammatory (Chavan & Hosamani, 2018), anti-HIV (Srivastav et al, 2018), antioxidant (P erez-Cruz et al, 2018), antimalarial (Hu et al, 2018), antitumor (Amin et al, 2018), anti-HCV (Peng et al, 2013), antihyperlipidemic (Iyer & Patil, 2014) and antitubercular (Patel et al, 2013) activities.…”
Section: Introductionmentioning
confidence: 99%